2007
DOI: 10.1007/s12149-007-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of treatment with donepezil hydrochloride and changes in regional cerebral blood flow in patients with Alzheimer's disease

Abstract: In cognitive function testing, the group that exhibited a complete response showed improvement primarily in parameters reflecting frontal lobe function. Complete responders also showed significantly greater blood flow increases in the basal ganglion and thalamus early during the treatment period. This indicates that the drug responsiveness of the basal ganglion and thalamus affects frontal lobe function and distinguishes complete responders from patients who do not exhibit such a response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 24 publications
3
59
0
Order By: Relevance
“…A Cochrane review found that the three compounds display a small but short-lived cognitive benefit (Birks, 2006). In light of renewed interest in the AD circulation, cholinesterase inhibitors were revisited and found to preserve or improve perfusion in AD patients undergoing therapy (Nakano et al, 2001;Nobili et al, 2002;Rosengarten et al, 2006;Bär et al, 2007;Yoshida et al, 2007) (Figure 4). In the study by Bär et al (2007), 5-week galantamine administration improved CO 2 reactivity as measured in the middle cerebral artery of 17 AD patients with transcranial Doppler sonography.…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane review found that the three compounds display a small but short-lived cognitive benefit (Birks, 2006). In light of renewed interest in the AD circulation, cholinesterase inhibitors were revisited and found to preserve or improve perfusion in AD patients undergoing therapy (Nakano et al, 2001;Nobili et al, 2002;Rosengarten et al, 2006;Bär et al, 2007;Yoshida et al, 2007) (Figure 4). In the study by Bär et al (2007), 5-week galantamine administration improved CO 2 reactivity as measured in the middle cerebral artery of 17 AD patients with transcranial Doppler sonography.…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 99%
“…This idea was further supported by the finding that patients whose cognitive score had stabilized or improved with cholinesterase inhibitor therapy, the so-called 'responders,' were also those who featured stabilized or increased perfusion, often within the first month of a 1-year treatment. Patients whose CBF had decreased during therapy were also those who had declined cognitively, the designated 'nonresponders' (Nakano et al, 2001;Nobili et al, 2002;Yoshida et al, 2007). The latter data highlighted the importance of targeting perfusion deficits as a means to influence mental status.…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 99%
“…The latter is portrayed functionally by a chronic cerebral hypoperfusion at rest and reduced perfusion to activated brain areas or impaired neurovascular coupling. Of interest, the decreases in cerebral blood flow (CBF) have been correlated with disease progression (Hirao et al, 2005) and with response to therapy (Yoshida et al, 2007). Recent evidence suggests that statins, cholesterol-lowering drugs broadly used in the treatment of cardiovascular diseases, have therapeutic potential in AD.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the effect of DNP on lifetime expectancy is not purely pharmacological. We previously reported [5] that the positive effects of SNH residency on AD were probably due to the following: First, DNP administration can improve psychomotor speed or attention [11,12], which is consistent with the higher mortality in older adults with lower perceptual speed [13]. Second, this improved cognitive function can smoothly lead to psychosocial intervention, and can increase the QOL.…”
Section: Positive Effect Of Dnp and Negative Effect Of Snh Residency mentioning
confidence: 57%